2018
DOI: 10.1155/2018/2178610
|View full text |Cite
|
Sign up to set email alerts
|

A Network Pharmacology Approach to Uncover the Potential Mechanism of Yinchensini Decoction

Abstract: Objective To predict and explore the potential mechanism of Yinchensini decoction (YCSND) based on systemic pharmacology. Method TCMSP database was searched for the active constituents and related target proteins of YCSND. Cytoscape 3.5.1 was used to construct the active ingredient-target interaction of YCSND and network topology analysis, with STRING online database for protein-protein interaction (PPI) network construction and analysis; and collection from the UniProt database of target protein gene name, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 33 publications
(30 reference statements)
0
22
0
Order By: Relevance
“…Although significant advances have been made in BC therapy with the advent of targeted therapies and immunotherapy, only a minority of patients benefit from the treatment and patient outcomes remain poor [ 3 ]. As a valuable alternative medicine, TCM has been associated with rich theoretical resources and invaluable experience that can be applied in clinical cancer therapy, and it has served as a vital resource for the development of multi-target drugs [ 19 ]. S. nigrum has been used to treat BC effectively [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although significant advances have been made in BC therapy with the advent of targeted therapies and immunotherapy, only a minority of patients benefit from the treatment and patient outcomes remain poor [ 3 ]. As a valuable alternative medicine, TCM has been associated with rich theoretical resources and invaluable experience that can be applied in clinical cancer therapy, and it has served as a vital resource for the development of multi-target drugs [ 19 ]. S. nigrum has been used to treat BC effectively [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…PPI network analysis revealed that the degree value of IL-6 was the highest, implying its role as a hub. The pro-inflammatory cytokine IL-6 has been established as one of the most biologically active cytokines with multiple biological functions [ 19 ]. Numerous studies have demonstrated that the aberrant expression of IL-6 and its receptor correlates with malignant phenotypes of multiple tumors, as well as the diagnosis, prognosis, and treatment of cancer [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al predicted the potential mechanism of Yinchensini decoction based on systemic pharmacology by using TCMSP database. We followed the methods of Chen et al [ 18 ]. From the TCMSP database, geniposide, gardenoside, geniposidic acid, genipin 1-gentiobioside, gardoside, and shanzhiside in Fructus Gardeniae from Jiangxi province are retrieved.…”
Section: Methodsmentioning
confidence: 99%
“…YGL is clinically used in combination with antiviral drugs to treat HB and can improve the rate of negative conversion. However, due to limitations in research techniques and economic considerations, research into the pharmacodynamics of traditional Chinese medicines (TCM) has been primarily focused on single targets or a few pathways [5,6]. It is difficult to reveal the synergy between multi-component and multiple targets in disease treatment.…”
Section: Introductionmentioning
confidence: 99%